2015
DOI: 10.1007/s00261-015-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT and MRI in the imaging assessment of cervical cancer

Abstract: Imaging plays a central role in the evaluation of patients with cervical cancer and helps guide treatment decisions. The purpose of this pictorial review is to describe magnetic resonance (MR) imaging and positron emission tomography (PET)/computed tomography (CT) assessment of cervical cancer, including indications for imaging, important findings that may result in management change, as well as limitations of both modalities. The International Federation of Gynecology and Obstetrics cervical cancer staging sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 70 publications
0
29
0
2
Order By: Relevance
“…In fact, a recent study performed by expert examiners confirmed these limitations 20 . However, as stated above, MRI also has limitations for this task 6 …”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In fact, a recent study performed by expert examiners confirmed these limitations 20 . However, as stated above, MRI also has limitations for this task 6 …”
Section: Discussionmentioning
confidence: 87%
“…Magnetic resonance imaging is currently considered the first‐line imaging technique for assessing the local extent in cervical cancer 6 , 7 . However, this technique has some limitations for assessing lymph node involvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Target delineation, choice of treatment technique and dose prescription for cervical cancer patients may all be influenced by PET-CT and might also obscure the comparability of treatment results between centres [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%